2018
DOI: 10.1002/micr.30335
|View full text |Cite
|
Sign up to set email alerts
|

Lower‐limb reconstruction with chimeric flaps: The quad flap*

Abstract: Early soft-tissue coverage is critical for treating traumatic open lower-extremity wounds. As free-flap reconstruction evolves, injuries once thought to be nonreconstructable are being salvaged. Free-tissue transfer is imperative when there is extensive dead space or exposure of vital structures such as bone, tendon, nerves, or blood vessels. We describe 2 cases of lower-extremity crush injuries salvaged with the quad flap. This novel flap consists of parascapular, scapular, serratus, and latissimus dorsi free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“… 1 , 3 The flexibility of design and customized insetting with spatial independence of each component has revolutionized the ability to reconstruct extensive/complex defects and optimize limb salvage outcomes. 3 , 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 , 3 The flexibility of design and customized insetting with spatial independence of each component has revolutionized the ability to reconstruct extensive/complex defects and optimize limb salvage outcomes. 3 , 5 …”
Section: Discussionmentioning
confidence: 99%
“…Subscapular artery system flaps are versatile and reliable workhorses for lower extremity reconstruction, offering a variety of separate components (muscle, skin, fascia, and scapular bone) joining a common pedicle. 1 , 3 , 5 , 9 The chimeric LD/SA/scapular/parascapular combined flap is considered the largest coverage option for complex 3-dimensional lower extremity defects. 1 , 9 The LD large dimensions for tibia resurfacing, the SA slips for malleolus coverage, and parascapular gliding surface for tendinous coverage suited perfectly the defect features in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bigdeli et al () reported that a conjoined parascapular and latissimus dorsi free flap is a large and reliable flap for simultaneous one‐stage reconstruction of complex and unusually large soft‐tissue defects in the knee region. Azouz et al (Azouz, Castel, Vijayasekaran, Rebecca, & Lettieri, ) described a quad flap, which consisted of contralateral composite parascapular and scapular fasciocutaneous flap and a serratus and latissimus dorsi muscle flap, for single‐stage large soft‐tissue coverage of extensive lower‐extremity injuries. However, those procedures often resulted in high donor site morbidity, a bulky appearance and an unstable mobile surface.…”
Section: Discussionmentioning
confidence: 99%
“…Large skin and soft-tissue defects in extremities are still challenges faced by plastic and reconstructive surgeons. With the development of reconstructive methods improved, chimeric, sequential, and combined perforator ap transplantation are ideal ways to repair large defects with its low donor site morbidities [1][2][3] . But surgical complexity, operation time, and tolerance of surgical procedures still need to be improved.…”
Section: Introductionmentioning
confidence: 99%